Ranks of the Divine Seekers: A Translation of Madārij al-Sālikīn bayna manāzil iyyāka naʿbudu wa-iyyāka nastaʿīn by Ibn Qayyim al-Jawziyya (d. 750/1351) : Volume 1 - Anjum, Ovamir, (Islamic Translation Series., 2020)
This is an unabridged, annotated, translation of the great Damascene savant and saint Ibn Qayyim al-Jawziyya's (d. 751/1350) Madārij al-Sālikīn. Conceived as a critical commentary on an earlier Sufi classic by the great Hanbalite scholar Abū Ismāʿīl of Herat, Madārij aims to rejuvenate Sufism's Qurʾanic foundations. The original work was a key text for the Sufi initiates, composed in terse, rhyming prose as a master's instruction to the aspiring seeker on the path to God, in a journey of a hundred stations whose ultimate purpose was to be lost to one's self ( fanāʾ ) and subsist ( baqāʾ ) in God. The translator, Ovamir (ʿUwaymir) Anjum, provides an extensive introduction and annotation to this English-Arabic face-to-face presentation of this masterpiece of Islamic psychology.